2019
DOI: 10.2147/ott.s195796
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long noncoding RNA HCP5 suppresses skin cutaneous melanoma development by regulating <em>RARRES3</em> gene expression via sponging miR-12</p>

Abstract: Objective This research aimed to investigate the role and mechanism of long noncoding RNA (lncRNA) HCP5 in skin cutaneous melanoma (SKCM). Materials and methods Survival analysis was performed using The Cancer Genome Atlas (TCGA)-SKCM data and SKCM patients’ clinical data. Primary SKCM cells were derived from patients’ pathologic tissue specimens. HCP5 overexpression was achieved by lentiviral transduction. Malignancy of SKCM cells was evaluated in vitro by cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…[19][20][21] Much evidence suggests that numerous lncRNAs are differentially expressed in melanoma, and their dysregulation is involved in melanoma progression because lncRNAs can act as oncogenic factors or tumor suppressors. [22][23][24] Accordingly, in-depth exploration of lncRNAs' functions in the formation and progression of melanoma is essential for identifying new targets for the diagnosis and management of this fatal disease.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Much evidence suggests that numerous lncRNAs are differentially expressed in melanoma, and their dysregulation is involved in melanoma progression because lncRNAs can act as oncogenic factors or tumor suppressors. [22][23][24] Accordingly, in-depth exploration of lncRNAs' functions in the formation and progression of melanoma is essential for identifying new targets for the diagnosis and management of this fatal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Three genes, i.e., CLEC7A , CLEC10A , and HAPLN3 have been reported to exhibit prognostic significance with respect to melanoma for the first time, while HCP5 has been reported to inhibit the development of cutaneous melanoma ( 42 ). CLEC7A (also known as dectin-1) encodes for a pattern-recognition receptor expressed by myeloid phagocytes (macrophages, dendritic cells, and neutrophils) that can directly drive the antimicrobial activity ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the long non-coding RNA (lncRNA) HCP5 in cancer remains controversial. Some reports suggest that HCP5 could induce tumor progression in cases of follicular thyroid carcinoma and lung adenocarcinoma ( 51 53 ), while others claim that HCP5 may suppress the development of cutaneous melanoma by modulating RARRES3 expression by sponging miR-12 ( 42 ). Consistent with previous studies, we observed an association between upregulated HCP5 expression and improved survival in melanoma and that HCP5 might boost the anti-tumoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lncRNA TTN-AS1 promotes SKCM development and metastasis by maintaining TTN expression ( Wang et al, 2020 ). LncRNA HCP5 inhibits the development of SKCM through regulation of miR-12 expression ( Wei et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%